(untitled) (Pubmet, 2022)
Helping publishers bring their authors’ work to life is at the heart of what we do at Kriyadocs. We do this through our offerings, which include our journal and book production platform and publishing services. As a publishing technology and service provider, our goals are to help publishers ▸ streamline their production workflows, ▸ publish high quality outputs, ▸ reach wider audiences faster, and ▸ scale their publications. Built by publishing experts in collaboration with publishers, Kriyadocs is the partner of choice for leading journal, book, and abstract publishers worldwide. We welcome you to join us in our PUBMET2022 sponsor workshop, where we will discuss the following aspects of our production platform and services: ▸ Automated manuscript conversion, styling, and editing ▸ XML-first workflows ▸ Project management ▸ Author proof reviews ▸ Metadata management ▸ Asset management ▸ Proof and output package generation ▸ Final delivery of outputs to hosting platforms and indexers ▸ Publishing services, including copyediting, typesetting, indexing, data conversion, and more Who is the workshop for? Any and all stakeholders managing or involved in the production workflows for journals and books are welcome to attend this workshop. Get in touch with us at hello@kriyadocs.com or visit www.kriyadocs.com, and let’s transform publishing together.